Conflict management and organizational climate: the mediation of motivation in a public higher education institution. - Rodríguez Montufar, Gilberto (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2026)
OBJECTIVE: To determine the effect of Conflict Management (CM) on Organizational Climate (OC) and to identify the mediating role of perceived work motivation (MOT) in a public higher education institution. MATERIAL AND METHOD: A quantitative, non-experimental, cross-sectional, and explanatory study was conducted with n = 96 employees (faculty and administrative staff). A Likert-scale questionnaire (1–5) was administered. The model was tested using PLS-SEM (PLSc) with bootstrapping (5,000 resamples). Reliability and validity were assessed (α, ω, CR ≥ 0.70; AVE ≥ 0.50; HTMT < 0.85), as well as predictive relevance (Q²). RESULTS: CM was positively associated with OC and with MOT; in turn, MOT was positively associated with OC. The indirect effect CM→MOT→OC was significant, indicating partial mediation by MOT and strengthening the explanation of OC. The results were stable in sensitivity analyses and showed no multicollinearity issues. CONCLUSIONS: CM, conceived as a management strategy, improves OC primarily through staff motivation. The findings provide useful evidence for designing institutional policies aimed at organizational well-being and for strengthening leadership training in collaborative conflict resolution.